Isolation of the ZmERS4 Gene From Maize and Its Functional Analysis in Transgenic Plants - Hang, Tianlu; Ling, Xuezhi; He, Cheng; Xie, Shanshan; Jiang, Haiyang; Ding, Ting (Frontiers in Microbiology, 2021)
A gene encoding a protein similar to ethylene receptor was isolated from maize (Zea mays L.), which was named as ZmERS4.The gene was 1,905 bp in length with an open reading frame that encoded a protein consisting of 634 amino acids. The homologous analysis showed that ZmERS4 shared high similarity with the ethylene receptor protein, OsERS1, from rice (Oryza sativa L.). ZmERS4 grouped into the ETR1 subfamily of ethylene receptors based on its conserved domain and phylogenetic status. Tissue-specific and induced expression analyses indicated that ZmERS4 was differentially expressed in maize tissues, predominantly in the stems and leaves, and was induced by salicylic acid (SA). Overexpression of ZmERS4 in Arabidopsis improved resistance against the bacterial pathogen, PstDC3000, by inducing the expression of SA signaling-related genes. Moreover, treatment with flg22 induced the expression of the defense-related gene, PR1, in maize protoplasts that transiently expressed ZmERS4. Furthermore, the ultra-high-performance liquid chromatography (UPLC) analysis showed that the SA contents in ZmERS4-overexpressing Arabidopsis lines were significantly higher than the control lines. Additionally, the improved resistance of ZmERS4-overexpressing Arabidopsis against PstDC3000 was blocked after pretreatment with the SA biosynthetic inhibitor, ABT. Based on the collective findings, we hypothesize that ZmERS4 plays an important role in disease resistance through SA-mediated signaling pathways.